War Crimes and Legal Accountability in the 2023 Israel-Gaza Conflict - Darnela, Lindra; Rusdiana, Erma; Sugitanata, Arif; Adawiah, Rabiatul (University of Jember, 2024)
This research focuses on the October 2023 conflict between Israel and Hamas, analyzing violations of international law committed by both parties under the 1949 Geneva Conventions. Using a qualitative document-based approach, the study investigates actions taken by Israel and Hamas during the first ten days of the conflict. It examines the jus ad bellum and jus in bello violations, such as Hamas's unprovoked attacks on Israeli civilians and Israel's disproportionate retaliatory strikes in Gaza. Both parties violated the Geneva Conventions: Hamas breached Article 51 by launching attacks without declaring war and targeting civilians. In contrast, Israel's retaliations violated the principle of proportionality by causing excessive civilian harm. Israel's blockade of Gaza also violated humanitarian law, as it denied civilians access to essential goods. The research identifies legal obligations under international law, noting that while Israel is a state party to the Geneva Conventions, Hamas, as a non-state actor, is bound by customary international law. The study concludes that both sides committed war crimes, requiring legal accountability through international mechanisms. The findings contribute to ongoing discussions about the challenges of enforcing international law in asymmetrical conflicts involving state and non-state actors.KEYWORDS: International law, Justice of war, Israel-Palestine dispute, Use of force.